Influence of nitrogen fertilization on the performance of early and late maturing maize varieties under natural infestation with Striga hermonthica (Del.) Benth - Kamara, A.Y.; Ekeleme, F.; Omoigui, L.O.; Menkir, A.; Chikoye, David; Dugje, I.Y.; Abdoulaye, Tahirou; Amaza, P. (Informa UK Limited, 2009)
Field studies were conducted in northeast Nigeria to evaluate the response ofearly and late-maturing maize varieties infested with natural populations ofStrigato different rates of nitrogen (N) fertilizer. There were significant reductions in thenumber of emergedStrigaat 120 kg N ha71for the early varieties and at 60 and120 kg N ha71for the late varieties. The number of emergedStrigaonlysignificantly differed among the late varieties. Averaged across varieties, grainyield of the early varieties was 144% higher at 60 kg N ha71and 192% higher at120 kg N ha71than without added N. For the late varieties the increase in grainyield was 85% higher at 60 kg N ha71and 144% higher at 120 kg N ha71thanwithout added N. Among the early varieties, TZE COMP4 C3 had significantlylower grain yield than the other varieties. Among the late varieties, grain yields of8338-1-1 and TZB-SR were significantly lower than in the other varieties. Ourresults show that the application of 60–120 kg N/ha toStrigaresistant or tolerantvarieties may reduce damage and increase grain yield. Higher economic rates ofreturn was obtained at N rates of 60–120 kg N/ha than the other rates.